Needs of Professional Formation in the field of Early Childhood: Perception and Contributions from the Students - Castillo-Cedeño, Rocío; Ramírez-Abrahams, Patricia; Ruíz-Guevara, Lilian Susana (Revista Electrónica Educare, 2017)
The analysis and information presented in this article are part of an experience developed in the research project Primera infancia: hacia una propuesta de formación contextualizada y pertinente [Early Childhood: Toward a Proposal of a Professional, Contextualized, and Pertinent Formation] of the Basic Education Division at the National University of Costa Rica. The information was collected with the purpose of identifying the needs for professional formation on the field of early childhood, through the perception and contributions of students in levels V and VII of their undergraduate degree in the Pedagogy career with a concentration in preschool education. This is an exploratory-type investigation aiming to know the opinions and perceptions of the students in relation with the process they go through at the university. For it, we used a questionnaire of seven open questions related to the needs of formation and concrete experiences lived during this process. As a result from this study, the analysis had a descriptive conclusion when exploring the main needs of the students. The information collected was complemented with the theory of investigation known, the contributions for the review of the whole preschool study plan, and all the knowledge built during the research project aforementioned. One of the main findings is that most of the students expressed that their formation lacks of the professional instrumentation to work with children aged zero to four years. They also said that it is very important to start working in a similar process on the earlier stages Pedagogy covers like maternal cycle and early stimulation. This systematization and analysis of the students’ perception is an effort to support the review of the study plan for the Pedagogy career with concentration in preschool education. The help of the students’ perceptions and experiences is a fundamental contribution in order to build a contextualized and relevant proposal; this is the main part of the research project aforementioned.